Stress and behavioral risk among young expectant couples. (December 2016) - Divney, Anna; Gordon, Derrick; Magriples, Urania; Kershaw, Trace
Abstract: Few studies have explored stress and coping among adolescents who are expecting a baby. In particular, young men's experiences during pregnancy have largely been ignored, despite the fact that a young man's experiences and behaviors carry implications for his own, his partner's and his child's health. This study examined the association between maternal and paternal experiences of stress during pregnancy with one's own and one's partner's health behaviors and depressive symptoms among 294 young expectant couples in the U.S. Multilevel modeling showed that one's own experiences of stress were associated with more unhealthy behaviors and more depressive symptoms among both expectant mothers and fathers. Paternal experiences of stress were predictive of more maternal conduct problems, while maternal experiences of stress were predictive of more paternal depressive symptoms and less paternal substance use. These findings highlight the importance of social relationships in affecting health behaviors and mental health among expectant adolescents.